KAJIAN FEMINISME CERPEN PASIEN KARYA DJENAR MAHESA AYU DAN IMPLIKASINYA TERHADAP PENGAJARAN SASTRA INDONESIA DI SEKOLAH - darussalam, zulfardi (Jurnal Curricula, 2017)
This research used to use socialistfeminism approach with descriptive qualitative method wich described the social phenomena in a short story Pasien by Djenar Mahesa Ayu. These phenomena are break down the patriarchal understanding of woman as mere objekct in interaction witch the male. The finding show that  atad feminism woman has the right to declare his existence in accordance with individualism  and women should bi able to find subjectivity it self.